Effect of loss-cone distribution on the generation of whistler waves in the magnetosphere - Tripathi A.K.; Misra K.D. (My University, 2025)
An anisotropic kappa velocity distribution with loss-cones is used to investigate whistler wave instability occurring in the magnetosphere. The elements of the dielectric tensor and dispersion relation using modified plasma dispersion function Zκ*(ξ) with loss-cone angle have been obtained for the linear waves propagating exactly parallel to a uniform local magnetic field in a homogeneous and hot plasma. The modified plasma dispersion function and integrals have been expressed in power-series form for argument of ξGt;1. Temporal/spatial growth rates for whistler wave in the magnetosphere have been evaluated by the method of numerical techniques. The results of such a kappa loss-cone distribution function on the generation of whistler waves are compared with those obtained by Maxwellian loss-cone distribution. Calculations show that either a loss-cone or a thermal anisotropy in the hot plasma component of the magnetosphere can lead to the generation of incoherent emission of low-frequency whistler waves. This methodology could be easily extended to the study of low frequency emissions from planetary magnetospheres under suitable choice of models of density and magnetic field and other plasma parameters. © 2004 Elsevier Ltd. All rights reserved.